2022
DOI: 10.3390/healthcare10030547
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Features and Potential Applications of PPG Signal in Healthcare: A Systematic Review

Abstract: Recent research indicates that Photoplethysmography (PPG) signals carry more information than oxygen saturation level (SpO2) and can be utilized for affordable, fast, and noninvasive healthcare applications. All these encourage the researchers to estimate its feasibility as an alternative to many expansive, time-wasting, and invasive methods. This systematic review discusses the current literature on diagnostic features of PPG signal and their applications that might present a potential venue to be adapted int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 211 publications
(389 reference statements)
0
24
0
Order By: Relevance
“…Examples of micromotion in daily life include tapping a foot, shaking a leg, wriggling in a chair, or the twitching of the eyes. Despite the common use of red and infrared light in pulse oximeters [ 46 ] because of their deeper tissue penetration than green light [ 47 , 48 , 49 ], green light is often utilized in commercial wearable devices such as smartwatches because of vast amount of existing knowledge of the technology [ 50 ]. Previous research has shown that green light has a higher signal-to-noise ratio (SNR) and more favorable physiological measurement results in environments with motion [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Examples of micromotion in daily life include tapping a foot, shaking a leg, wriggling in a chair, or the twitching of the eyes. Despite the common use of red and infrared light in pulse oximeters [ 46 ] because of their deeper tissue penetration than green light [ 47 , 48 , 49 ], green light is often utilized in commercial wearable devices such as smartwatches because of vast amount of existing knowledge of the technology [ 50 ]. Previous research has shown that green light has a higher signal-to-noise ratio (SNR) and more favorable physiological measurement results in environments with motion [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The performance of the proposed method is evaluated using the following two performance metrics: MSE: 2 , and peak signal-to-noise ratio (PSNR): = 10log 10 (1 MSE) in decibels, where x j is the clean PPG signal, xj is denoised PPG signal, and M is the batch size.…”
Section: Performance Metricsmentioning
confidence: 99%
“…to monitor various important physiological parameters, e.g., heart rate, heart rate variability, blood Oxygen saturation level (SpO2), and respiratory rate [1]. More recently, the PPG signal has been used to aid in the diagnosis of several cardiac vascular, respiratory, and neurological diseases [2].…”
Section: Introductionmentioning
confidence: 99%
“…These factors can render such procedures hardly accessible to specific segments of the population, such as skin skin-sensitiveness. Researchers also introduced photoplethysmography-based 6,7 contact devices to monitor CVD continuously. However, these devices have significant drawbacks for patients with sensitive skin, as they may experience irritation reactions after prolonged wear.…”
Section: Introductionmentioning
confidence: 99%